Salivary metabolomic biomarkers for esophageal and gastric cancers by liquid chromatography–mass spectrometry - Nakane, Kosuke; Yagi, Koichi; Yajima, Sho; Nomura, Sachiyo; Sugimoto, Masahiro; Seto, Yasuyuki (Cancer Science, 2024)
Early detection of esophageal and gastric cancers is essential for patients' prognosis; however, optimal noninvasive screening tests are currently not available. Saliva is a biofluid that is readily available, allowing for frequent screening tests. Thus, we explored salivary diagnostic biomarkers for esophageal and gastric cancers using metabolomic analyses. Saliva samples were collected from patients with esophageal (n = 50) and gastric cancer (n = 63), and patients without cancer as controls (n = 20). Salivary metabolites were analyzed by liquid chromatography–mass spectrometry to identify salivary biomarkers. We also examined the metabolic profiles of gastric cancer tissues and compared them with the salivary biomarkers. The sensitivity of the diagnostic models based on salivary biomarkers was assessed by comparing it with that of serum tumor markers. Additionally, using postoperative saliva samples collected from patients with gastric cancer, we analyzed the changes in the biomarkers' concentrations before and after surgery. Cytosine was detected as a salivary biomarker for gastric cancer, and cytosine, 2‐oxoglutarate, and arginine were detected as salivary biomarkers for esophageal cancer. Cytidine, a cytosine nucleotide, showed decreased concentrations in gastric cancer tissues. The sensitivity of the diagnostic models for esophageal and gastric cancers was 66.0% and 47.6%, respectively, while that of serum tumor markers was 40%. Salivary cytosine concentration increased significantly postoperatively relative to the preoperative value. In summary, we identified salivary biomarkers for esophageal and gastric cancers, which showed diagnostic sensitivity at least comparable to that of serum tumor markers. Salivary metabolomic tests could be promising screening tests for these types of cancer. We explored salivary diagnostic biomarkers for esophageal and gastric cancers using liquid chromatography–mass spectrometry. Cytosine was detected as a salivary biomarker for gastric cancer, and cytosine, 2‐oxoglutarate, and arginine were detected as salivary biomarkers for esophageal cancer. The diagnostic ability of the models constructed with the detected biomarkers was at least equivalent to that of serum tumor markers.